Bridging the gaps in inpatient tobacco dependency management: a quality improvement project - Chaw Hsu; Myat Thin; Muhammad Arif (Future Healthcare Journal)
Introduction: Tobacco smoking remains one of the leading causes of preventable mortality, significantly contributing to cancer, respiratory and cardiovascular diseases. Hospitalisation presents a critical opportunity to support smoking cessation through structured interventions.1 However, gaps in inpatient tobacco dependency management persist, impacting the effectiveness of cessation efforts. Aims and objectives: This quality improvement project aimed to evaluate the impact of targeted interventions on smoking status documentation, delivery of Very Brief Advice (VBA), initiation of Nicotine Replacement Therapy (NRT) and referral rates for cessation services. Two audit cycles were conducted to measure improvements and enhance adherence to British Thoracic Society (BTS) guidelines.2 Methods: A retrospective analysis of electronic patient records was performed for 198 inpatients in May 2024 and 100 inpatients in September 2024 following interventions. Key parameters assessed included smoking status documentation, VBA provision, NRT prescription rates and referral rates to smoking cessation services.Interventions implemented between audit cycles included staff education sessions, informative posters and enhanced training support, aligned with the updated BTS statement on Inpatient Tobacco Dependency Management. Results: Of the 298 audited patients, smoking status was documented for 178 individuals: 49.4% were non-smokers (88/178), 18.5% were current smokers (33/178) and 32.0% were ex-smokers (57/178). Among current smokers, 5.1% (9/178) were female and 13.5% (24/178) were male.Following the interventions, smoking status documentation improved from 55% (109/198) to 69% (69/100). VBA provision increased from 14% to 27%, although it remained below the BTS target of 90%. NRT initiation rates also rose from 14% to 27%, and referrals for smoking cessation support improved from 5% to 9%.Despite these gains, several challenges hindered further progress. The rotational nature of hospital staffing led to inconsistent implementation of interventions. Additionally, the absence of an in-house smoking cessation team limited the sustainability of improvements. Conclusion: Targeted interventions successfully enhanced smoking status documentation, VBA delivery and NRT initiation. However, these measures fell short of BTS standards, highlighting the need for sustained efforts. Establishing dedicated smoking cessation teams, improving staff engagement and integrating smoking cessation strategies into routine care are crucial to bridging the remaining gaps. Addressing structural barriers and ensuring ongoing staff education will be essential for achieving long-term improvements in inpatient tobacco-dependency management.